2020
DOI: 10.1167/iovs.61.8.36
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Intraocular Pressure-Induced Changes in Schlemm's Canal Morphology on Outflow Facility in Healthy Human Eyes

Abstract: Purpose To estimate the outflow facility coefficient (C) as a function of Schlemm's canal cross-sectional area (SCAR) in healthy subjects using noninvasive oculopression tonometry (OPT). Methods In 25 healthy volunteers, intraocular pressure (IOP) decay values were recorded by a ophthalmodynamometer, with a fixed external force (0.15 N) on the inferior-temporal eyelid, every 10 seconds, for four minutes, and again after a 30-minute rest. Schlemm's canal profile images a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…While the SC area remained stable in the placebo group, the SC lumen expanded obviously, and the IOP decreased in the travoprost-treated group; the expansion effect was maintained up to 60 h after administration. However, this expansion was reversed to the baseline from 72 h. In line with this finding, it has been reported that IOP reduction leads to SC area expansion and vice versa 20 , 24 , 25 . Based on microsurgical and perfusion study, Johnstone and Grant 24 reported that the diameter of the SC lumen was IOP-dependent and reached a minimum at high pressures but was enlarged under low pressure.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…While the SC area remained stable in the placebo group, the SC lumen expanded obviously, and the IOP decreased in the travoprost-treated group; the expansion effect was maintained up to 60 h after administration. However, this expansion was reversed to the baseline from 72 h. In line with this finding, it has been reported that IOP reduction leads to SC area expansion and vice versa 20 , 24 , 25 . Based on microsurgical and perfusion study, Johnstone and Grant 24 reported that the diameter of the SC lumen was IOP-dependent and reached a minimum at high pressures but was enlarged under low pressure.…”
Section: Discussionsupporting
confidence: 84%
“…Based on microsurgical and perfusion study, Johnstone and Grant 24 reported that the diameter of the SC lumen was IOP-dependent and reached a minimum at high pressures but was enlarged under low pressure. In another study, Chen and colleagues 25 showed the link between the collapse of SC and decrease in outflow facility with acute IOP increase. Further, Hong et al 14 reported that the degree of SC expansion was related to the extent of IOP decrease after trabeculectomy in patients with glaucoma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…During the course of this project, Chen et al 12 reported a decline in IOP during a 4-min ocular compression. The dimensions of the Schlemm's canal were monitored using SD-OCT.…”
Section: Discussionmentioning
confidence: 96%
“…Older adults, particularly POAG patients, should be recruited in future study. Measurement of the Schlemm's canal was not included and the change of Schlemm's canal dimension and IOP variation was based on the previous study by Chen et al 12 Investigators using ocular compression to study LC shape should measure IOP at both the initial and nal stages of ocular compression.…”
Section: Discussionmentioning
confidence: 99%